2007
DOI: 10.2353/ajpath.2007.061006
|View full text |Cite
|
Sign up to set email alerts
|

Tonsil Epithelial Factors May Influence Oropharyngeal Human Immunodeficiency Virus Transmission

Abstract: Tonsil epithelium has been implicated in human immunodeficiency virus (HIV) pathogenesis, but its role in oral transmission remains controversial. To study characteristics of this tissue, which may influence susceptibility or resistance to HIV, we performed microarray analysis of the tonsil epithelium. Our data revealed that genes related to immune functions such as antibody production and antigen processing were increasingly expressed in tonsil compared with the epithelium of another oropharyngeal site, the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…For example, several studies have concluded that SLPI levels are decreased in cervical secretions and saliva of HIV-1 infected individuals. 29-33 However, other studies have indicated that HIV-1 infection may increase salivary SLPI. 40,41 For these reasons, in the current study we chose to investigate SLPI levels in an HIV + cohort to reduce potential confounding.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies have concluded that SLPI levels are decreased in cervical secretions and saliva of HIV-1 infected individuals. 29-33 However, other studies have indicated that HIV-1 infection may increase salivary SLPI. 40,41 For these reasons, in the current study we chose to investigate SLPI levels in an HIV + cohort to reduce potential confounding.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that EBV glycoproteins may not play major roles in viral macropinocytosis from the apical surface of tonsil epithelial cells and that other mechanisms could be involved in this process. It has been reported that tonsil epithelium expresses the Fc receptor FC␥III (121), which may facilitate apical to basolateral transcytosis of IgG-coated EBV virions. A similar mechanism has been shown for HCMV: the neonatal Fc receptor facilitates apical to basolateral transcytosis of IgG-coated HCMV in placental epithelial cells (56).…”
Section: Cd19mentioning
confidence: 99%
“…In healthy individuals, these normal flora prevent colonization by invading organisms by changing the local pH, by producing bacteriocins, and by providing a mechanical barrier that prevents adherence to mucosal surfaces (2,4,5). The oropharynx is also a reservoir for several viruses, including HIV, as well as for papillomaviruses and Epstein-Barr virus, which are associated with oropharyngeal carcinomas (6)(7)(8)(9). Although oropharyngeal and oral microbes in general have been studied extensively using culturing and 16S sequencing, little is known about viral communities in the oropharyngeal spaces of healthy individuals (1,(10)(11)(12)(13).…”
mentioning
confidence: 99%